Two-Step Proximal Method for Equilibrium Problems in Hadamard spaces - Vedel, Yana I.; Semenov, Vladimir V.; Golubeva, Kateryna M. (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
We propose a novel two-step proximal method for solving equilibrium problems in Hadamard spaces. The equilibrium problem is very general in the sense that it includes as special cases many applied mathematical models such as: variational inequalities, optimization problems, saddle point problems, and Nash equilibrium point problems. The proposed algorithm is the analog of the two-step algorithm for solving the equilibrium problem in Hilbert spaces explored earlier. We prove the weak convergence of the sequence generated by the algorithm for pseudo-monotone bifunctions. Our results extend some known results in the literature for pseudo-monotone equilibrium problems.